Investigating performance of a novel safety measure for assessing potential rear-end collisions: An insight representing a scenario in developing nation. (April 2022) - Raju, Narayana; Arkatkar, Shriniwas S.; Easa, Said; Joshi, Gaurang
Abstract: Road safety is one of the major concerns in the ever-growing traffic network. In addressing this, surrogate safety measures play a critical role in identifying collision instincts. Besides the added advantage of quantifying collision instincts in advance, surrogate safety measures have their limitations. For example, in some instances, those measures tend to show erroneous results. In this paper, a new surrogate safety measure Instant Heeding Time (IHT), is presented based on follower vehicle attention in the traffic streams. This new measure is integrated with a distance gap and the vehicles' speeds to assess probable rear-end collisions. Further, along with other safety measures, the developed safety framework is tested over a study section, with the help of trajectory datasets at three traffic flow conditions (free flow, capacity, and congested) under prevailing heterogeneous (mixed) traffic conditions. Based on the safety framework, it is observed that, in the case of free flow and capacity conditions, 23 and 55 probable rear-end collisions points are detected. At the congested conditions, no rear-end collision points are observed. Further, smaller vehicles in the traffic stream are associated with a higher number of rear-end collision instincts than other vehicle categories. The conceptualized safety framework can be applied on a real-time basis for monitoring the safety measures for vehicles in a mixed traffic stream. Highlights: A new surrogate safety measure Instant Heeding Time (IHT), is compared with the established surrogate safety measures for assessing the rear-end collision instincts. The conceptualized safety framework in the study can be applied on a real-time basis for monitoring the safety measures for vehicles in a mixed traffic stream. It was observed that safety over the traffic stream is one of the most sensitive parameters of a road network, which can be affected by any means and decisively can influence the road network performance. Advocated the importance of trajectory data in understanding the traffic at its best. The study demonstrated the limitations of the present existing surrogate safety measures.